Dividend policy influence stock price volatility of telecommunication industry in Malaysia / Shahirin Abd Latip - Abd Latip, Shahirin (Faculty of Business Management, 2017)
Share prices are the most important indicators used by investors to invest or not to invest on a particular share. The main objective of the investing is to maximize the expected return at the low level of risk. There are many factors contributed to the price changes of share include investor’s reaction towards earnings, dividend or other news. According to the efficient market hypothesis, when there is new information either good or bad news are available to the public, they will affect share price of the company. Thus, aim of this study is to determine the effect of dividend policy towards share price of the Telecommunication companies in Malaysia. We look into five Telecommunication companies that are listed in Bursa Malaysia. The data for this study is a secondary data that collected from DataStream. The duration of this study will be from 2010 until 2015. Panel Data analysis has been applied and various methods in order to test the significant of the variables towards the price volatility of Telecommunication companies. The finding of this study shows that there is a significant positive relationship between the DPR of a firm and share price volatility. This result is consistent with (Zakaria, Muhammad, & Zulkifli, 2012). DY is insignificant and positively related to the movement of stock prices. Thus, this finding suggests that, higher DPR will lead to a more volatile share prices. Among the control variables, only firm size (NI) and leverage (DER) showed high correlation with the changes of the firm share prices. The larger the size of the company, the greater the company needs to face with the volatility of share prices. The results show all variables are significant except variable DY on the changes of the company share prices. The contradiction could be because of the different economics and business environments of the countries.